Towards a Stable Layered Vanadium Oxide Cathode for High‐Capacity Calcium Batteries. Issue 43 (30th June 2022) - Zhang, Xiao; Xu, Xiaoming; Song, Bo; Duan, Manyi; Meng, Jiashen; Wang, Xuanpeng; Xiao, Zhitong; Xu, Lin; Mai, Liqiang
Abstract: Calcium‐based batteries have promising advantages over multivalent ion batteries. However, the fabrication of highly efficient calcium batteries is limited by the quality of available cathode materials, which motivates the exploration of electrodes that can enable reversible, stable Ca 2+ intercalation. Herein, layered vanadium oxide Mg x V2 O5 · n H2 O is used as a calcium battery cathode, and it exhibits a high capacity of 195.5 mA h g −1 at 20 mA g −1 and an outstanding cycling life (93.6% capacity retention after 2500 cycles at 1 A g −1 ). Combining theoretical analysis and experimental design, a series of layered oxides (M x V2 O5 · n H2 O, M = Mg, Ca, Sr) is selected as a model system to identify the Ca storage mechanism. It is found that the hydrated alkaline earth metal ions in the vanadium‐based layered oxide interlayers play a critical role as pillared stabilizers to facilitate Ca 2+ insertion/extraction. Compared with Ca 2+ and Sr 2+, the presence of Mg 2+ provides vanadium oxides with a rigid framework that allows for minimized volume fluctuation (a tiny variation of ≈0.15 Å of the interlayer spacing). Such an understanding of the Ca storage mechanism is a key step in the rational design and selection of materials for calcium batteries to achieve a high capacity and long cycle life. Abstract : Alkaline earth metal‐ion preintercalated bilayered vanadium oxide (M x V2 O5 · n H2 O, M = Mg, Ca, Sr) nanowires are demonstrated as cathodes for calcium batteries. The structural stability and Ca 2+ storage properties of M x V2 O5 · n H2 O are fully proved by experiments and theoretical calculation, and batteries based on the Mg x V2 O5 · n H2 O cathode with exceptional lifespan are delivered.